2018
DOI: 10.1007/s10067-018-4019-0
|View full text |Cite
|
Sign up to set email alerts
|

Ear, nose and throat involvement in granulomatosis with polyangiitis: how it presents and how it determines disease severity and long-term outcomes

Abstract: Ear, nose and throat (ENT) manifestations in granulomatosis with polyangiitis (GPA) represent the most frequent symptoms at disease onset. The aim of the study was to analyse ENT involvement at diagnosis, as well as how it could influence relapse rate, mortality and disease severity. A retrospective non-controlled cohort study was performed including all consecutive diagnosed GPA from 1996 to 2016 in two rheumatology centres of Northern Italy, focusing particularly on ENT presenting signs and symptoms at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 33 publications
5
37
2
2
Order By: Relevance
“…Sinusitis and nasal inflammation were found in 30.4% of our patients. These figures are lower than those reported elsewhere [10,15,16]. Likewise all other sino nasal symptoms occurred less frequently in our patients compared to other studies [15,16].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Sinusitis and nasal inflammation were found in 30.4% of our patients. These figures are lower than those reported elsewhere [10,15,16]. Likewise all other sino nasal symptoms occurred less frequently in our patients compared to other studies [15,16].…”
Section: Discussioncontrasting
confidence: 88%
“…A study from Tunisia has reported initial ENT involvement of 56% and 83% at follow up [17]. Nose and sinus are reported to be affected by GPA in 55-90% of patients, which is comparable to our finding of 56.5% [8,9,16,18]. Nasal crusting and obstruction, rhinorrhea, nasal discharge, epistaxis, sinusitis, nasal septum deviation and perforation, edema of nasal mucosa and turbinates, and saddle nose deformity are frequently reported sino nasal symptoms [19,20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…PR3 ANCA positive 56%-83% 8,14 ANCA Negative 11%-31% 14,25 ENT involvement 70%-99% 13,26 Rhinologic Sinus involvement/Rhinitis 47%-72% 8,25 Recurrent epistaxis/nasal crusting 28%-83% 25,27 Nasal cavity adhesions 19%-26% 18,28 Rhinorrhoea 35%-54% 25,28 Mucosal ulcerations/granulations 10%-27% 18,28 Nasal septal perforation 8%-33% 27,29 External nasal/Saddle deformity 2%-22% 27,29 Epiphora 13% 29…”
Section: Prevalence Of Ent Features Of Granulomatosis With Polyangiitismentioning
confidence: 99%
“…Cranial nerve palsy 17% 33 Subglottic stenosis 1%-23% 18,27 Abbreviations: CHL, conductive hearing loss; OME, otitis media with effusion; SNHL, sensorineural hearing loss; VC: vocal cord.…”
Section: Prevalence Of Ent Features Of Granulomatosis With Polyangiitismentioning
confidence: 99%